PENGARUH TINGKAT LEVERAGE, UKURAN DEWAN KOMISARIS, DAN STRUKTUR KEPEMILIKAN SAHAM PERUSAHAAN TERHADAP CSR DISCLOSURE - Yudi Prasetyo (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aimed to analyze and get empirical evidence about influence of the level of leverage, size of board of commissioner, and ownership structure have affect to corporate social responsibility disclosure in the property and real estate company in Indonesia. ownership structure, which in proxy is managerial ownership, public ownership and foreign ownership. The research is done at property and real estate company which are listed in Indonesia Stock Exchange from periode 2010 until 2014. This research used purposive sampling It was found 27 company at the research sampel ang then the total sampel for 5 years is 135 sampel . This research used Multiple Regression Analysis Method. The result this research showed size of board of commissioner, Publik Ownership and Foreign Ownership significant influence for corporate social responsibility disclosure while the level of leverage and m.anagerial ownership not significant influence for corporate social responsibility disclosure